Konsep Perencanaan Permukiman Tepi Sungai Yang Berwawasan Ekologi - Bambang Daryanto; Rudi Hartono (Universitas Lambung Mangkurat, 2003)
The concept of sustainable development is how a development can be conducted without going beyond the capacity of natural support for current and future life. Environmentally-aware residential planning and occupancy-worthy should support the hygiene and comfort of the environment, supporting environmental preservation. All are shown in the case study on a residential area along Kuin river, Banjarmasin. The problem is how the concept of residential planning that involves the preservation of the function and balance of the living environment inside an ecosystem should be established. The planning objective is to establish a residential development which involves spatial planning which considers ecological concept. The target of the residential planning is to use the land in accordance with support capacity, area, avoiding environmental degradation, creating a balance living environment, comfortable environment, interesting and processing identity.The approach and planning strategy being used are planning concept with ecological consideration based on relationship between living creatures and their environment, and planning concept based on cultural and natural resource management. The residential planning concept is directed to the concept of natural resource ecosystem and built environtment that is site planning and environmental consideration of the site. The conclusions of research are that rivers in urban scale is included in urban open space, the river banks are lack of vegetation, residential housing along river banks to increase river pollution level, alternatives on new building material are necessary due due to the scarce availability of local timber.